UTILIZING PLASTIC WASTE AS A VILLAGE LANDMARK THROUGH ECOBRICK TECHNOLOGY - Stefanus H Gusti Ma; Ana Maria Gadi Djou; Helena Rosalia Parera; Maria Kristina Ota; Sayful Amrin; Marsel Nande; Yohanes Kapistrano Dhajo; Agustinus Minu Kwure; Maria Lidwina Deze; Marianus Kejapilus Naga (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
Plastic waste management is one of the environmental problems that continues to grow in rural areas, including in Dile Village, Detusoko District, Ende Regency, East Nusa Tenggara. This community service activity aims to utilize plastic waste into Ecobricks as material for making the Dile Village name icon, develop sustainable environmental education media, and increase public participation and awareness in plastic waste management. The activity was carried out on June 13, 2026, at the Dile Village office by 24 Semester VI students of the Economic Education Study Program, University of Flores, accompanied by lecturers. The method used is an implementative approach based on active participation with participatory observation, interviews, and documentation techniques. The program was implemented through six stages, namely committee formation, initial observation, coordination with the village government, Ecobrick production, evaluation, and icon installation. The results of the activity showed that 700 plastic bottles were successfully processed into Ecobricks and assembled into an icon written "DILE VILLAGE", which was installed at the Dile Village Office. The presence of this icon has received a positive response from village officials and the community, as it strengthens the village's visual identity and serves as an educational tool regarding the importance of educational, aesthetic, and sustainable waste management. As a follow-up, this program is recommended for further development through community and village government involvement and replication in other villages facing similar plastic waste issues.